Yash singh Sengar Asked a Question
August 10, 2020 7:55 pmpts 30 pts
Solution of+y")dr = (tan y-x)dy is (A) x= tan y-1+ ce- (C)x= tan'y+ce" -tany (B) y= tan y-1+ ce (D).x = tan y+1+cey
  • 2 Answer(s)
  • 0 Likes
  • 3 Comments
  • Shares
  • Vishal goswami Best Answer
    see attachment
    • cropped6760506881825631604.jpg
    Likes(0) Reply(1)
    Vishal goswami
    if you have any doubt then please ask.
  • Ruby negi thankyou
    easy question...
    • cropped-2018698851.jpg
    Likes(1) Reply(1)
    Ruby negi
    using linear differential..
  • Vishal goswami
    see attachment
    • cropped7400382142859309224.jpg
    Likes(0) Reply(0)